Ruxolitinib for chronic steroid-refractory graft versus host disease: a single center experience. (October 2021) - Xue, Elisabetta; Lorentino, Francesca; Pavesi, Francesca; Assanelli, Andrea; Peccatori, Jacopo; Bernardi, Massimo; Corti, Consuelo; Ciceri, Fabio; Lupo Stanghellini, Maria Teresa
Highlights: Chronic GvHD complicates up to 70 % of allogeneic hematopoietic transplant. About 60 % of patients with chronic GvHD will need more than one line of treatment. JAK1–2 inhibitor ruxolitinib is safe and effective in chronic GvHD that failed multiple prior lines. Major responses were seen in cutaneous, oral, genital tract and ocular GvHD. Abstract: Background: Chronic Graft versus Host Disease (GvHD) is a serious complication of allogeneic hematopoietic stem cell transplant that severely impacts quality of life and long-term survival. About 50-to-60 % of patients treated with steroids require a further line of therapy due to lack of sustained response. Ruxolitinib, a JAK1/2 inhibitor, has recently been approved for the treatment of acute GvHD. Methods: We aimed to retrospectively evaluate ruxolitinib efficacy and safety in a cohort of patients diagnosed with moderate (25 %) or severe (75 %) steroid-refractory or steroid-dependent chronic GvHD. Response evaluation was performed at three and six months. Results: Thirty-six patients received ruxolitinib after a median of three previous lines (range, r 1–11) for a median of 8.6 months (r 1–51.6). Cutaneous GvHD was the most frequent presentation. We observed an overall response of 59 % (CR 9%, PR 50 %) at three months and 62 % (CR 15 %, PR 46 %) at six months. Two patients had hematologic disease recurrence and were censored at relapse; no other permanent discontinuation due to adverse events were documented. Cutaneous, oral, genital and ocular GvHD significantly improved after treatment. 2-year overall survival and 2-year transplant related mortality were 74 % and 19 % respectively. Ruxolitinib was associated with a significant reduction of steroid dose. Conclusion: Ruxolitinib was confirmed to be a safe and effective option as salvage treatment also for advanced stages of chronic GvHD. Longer follow up is needed to evaluate durability of response. Prospective analyses on larger cohorts are ongoing.